2007
DOI: 10.5172/conu.2007.25.1-2.163
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s not easy’: Caring for Aboriginal clients with diabetes in remote Australia

Abstract: This paper presents a personal perspective of caring for clients with diabetes on a remote Aboriginal community in the Northern Territory. The state of Aboriginal health in Australia is explored and consideration given to Government recommendations targeting the improvement of health in the Indigenous population. For the remote area nurse at the grass roots, the application of these recommendations is not always easy. The recommendations can be both impractical and irrelevant in remote areas where resources ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Many health professionals acknowledged the challenges faced by Indigenous Australians taking long-term medicines, but there were mixed views on patients’ attitudes to medicines and adherence [ 29 – 31 ]. No studies reported patients’ own perceptions of their adherence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many health professionals acknowledged the challenges faced by Indigenous Australians taking long-term medicines, but there were mixed views on patients’ attitudes to medicines and adherence [ 29 – 31 ]. No studies reported patients’ own perceptions of their adherence.…”
Section: Resultsmentioning
confidence: 99%
“…An issue reported by patients only was forgetting to take doses [ 31 , 40 , 45 , 46 ] and a few participants stated that their belief in God meant they did not need to take medicines [ 44 – 46 ]. In addition, health professionals reported that inadequate safe storage for medicines at home impaired adherence [ 30 , 47 ].…”
Section: Resultsmentioning
confidence: 99%